Serum MG53/TRIM72 Is Associated With the Presence and Severity of Coronary Artery Disease and Acute Myocardial Infarction - Xie, Hongyang; Wang, Yaqiong; Zhu, Tianqi; Feng, Shuo; Yan, Zijun; Zhu, Zhengbin; Ni, Jingwei; Ni, Jun; Du, Run; Zhu, Jinzhou; Ding, Fenghua; Liu, Shengjun; et al. (Frontiers in Physiology, 2020)
Background: Mitsugumin 53 or Tripartite motif 72 (MG53/TRIM72), a myokine/cardiokine belonging to the tripartite motif family, can protect the heart from ischemic injury and regulate lipid metabolism in rodents. However, its biological function in humans remains unclear. This study sought to investigate the relationship between circulating MG53 levels and coronary artery disease (CAD). Methods: The concentration of MG53 was measured by enzyme-linked immunosorbent assay (ELISA) in serum samples from 639 patients who underwent angiography, including 205 controls, 222 patients with stable CAD, and 212 patients with acute myocardial infarction (AMI). Logistic and linear regression analyses were used to analyze the relationship between MG53 and CAD. Results: MG53 levels were increased in patients with stable CAD and were highest in patients with AMI. Additionally, patients with comorbidities, such as chronic kidney disease (CKD) and diabetes also had a higher concentration of MG53. We found that MG53 is a significant diagnostic marker of CAD and AMI, as analyzed by logistic regression models. Multivariate linear regression models revealed that serum MG53 was significantly corelated positively with SYNTAX scores. Global Registry of Acute Coronary Events (GRACE) scores also correlated with serum MG53 levels, indicating that MG53 levels were associated with the severity of CAD and AMI after adjusting for multiple risk factors and clinical biomarkers. Conclusion: MG53 is a valuable diagnostic marker whose serum levels correlate with the presence and severity of stable CAD and AMI, and may represent a novel biomarker for diagnosing CAD and indicating the severity of CAD.